Business plans handbook. a compilation of actual business plans developed by small businesses throughout North America - Kahrs, Kristin, 1967- (Gale virtual reference library, 1996)
Collection of actual business plans from businesses in the manufacturing, retail and service industries, with company names and addresses changed. Includes: business plan template, fictional business plans, listing of organizations, agencies, and consultants; a glossary; and an updated bibliography. Aimed at entrepreneurs seeking funding for small businesses in North America.